Pengaruh Diskon, Kualitas Produk, dan Gaya Hidup Terhadap Keputusan Impulse Buying Konsumen Produk UNIQLO - Yuni Yuniawati; Istichanah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The population in this study are consumers of Uniqlo AEON Mall products West Tanjung branch as many as 100 respondents. The research method used the researcher is the slovin method of the tests carried out are: validity test, test reliability, normality test, multicollinearity test, heteroscedasticity, linear regression analysis multiple, t test, f test, and the coefficient of determination. Testing tools used is SPSS 26 software for windows. The results of this study indicate that partially discounts have a positive effect on Impulse Buying decisions, partially Product Quality has an effect positive towards Impulse Buying decisions, partially influential Lifestyle positive towards Impulse Buying decisions, simultaneously Discounts, Product Quality, and Lifestyle influence on consumer Impulse Buying decisions Uniqlo products, then the percentage of contributions to the influence of the independent variables includes Discounts, Product Quality, and Lifestyle on the dependent variable Impulse Buying is 0.788 or 78.8%.